Efek Hepatoprotektor Ekstrak Etanol Daun Pucuk Merah (Syzygium campanulatum (Korth) dan Daun Cengkeh (Syzygium aromaticum (L.) Merr. & L. M. Perry) pada Tikus Jantan Galur Wistar (Rattus norvegicus) yang diinduksi Paracetamol - Much Ilham Novalisa Aji Wibowo; Nur Aeni; Zidna Mazayatul Huda; Nunuk Aries Nurulita (Fakultas Farmasi Universitas Pancasila, 2017)
Syzygium campanulatum and Syzygium aromaticum contains antioxidant components suchas flavonoids, phenolic, and terpenoids. May have hepatoprotective properties in reducing SGPT and SGOT activity. This research wants to determine the potency of hepatoprotective of ethanolic extract of Syzygium campanulatum (Korth) and Syzygium aromaticum leaf compared with curcuma tablets. This research uses 24 male Wistar rats divided into 6 groups: I, II, III (as a normal, induction, and compared control), group IV, V, VI were treated 105, 210, and 420 mg/kg BW respectively. The study was conducted for 9 days. After 7 days of treatment, treated groups were exposed by hepatotoxic dose of paracetamol (2000 mg/kg BW). The SGPT and SGOT activity of all groups was measured by enzimatic assay. The result can be concluded that Syzygium campanulatum extract was found to be active as hepatoprotective agent with 210 mg/kg BW dosage (SGPT 21.76 ± 3.98 U/L and SGOT 7.32±6.74U/L) as eff ective as with the curcuma tablets (SGPT 23.91 ± 4.41 U/L and SGOT 14.12±5.37 U/L) and the hepatoprotective activity of Syzygium campanulatum extract at a dosage 420 mg/kg BW better than curcuma tablets (SGPT 12.43 ± 6.51 U/L and SGOT 6.64 ± 5.88 U/L). While the hepatoprotec Syzygium campanulatum and Syzygium aromaticum contains antioxidant components such as flavonoids, phenolic, and terpenoids.May have hepatoprotective properties in reducing SGPT and SGOT activity. This research wants to determine the potency of hepatoprotective of ethanolic extract of Syzygium campanulatum (Korth) and Syzygium aromaticum leaf compared with curcuma tablets. This research uses 24 male Wistar rats divided into 6 groups: I, II, III (as a normal, induction, and compared control), group IV, V, VI were treated 105, 210, and 420 mg/kg BW respectively. The study was conducted for 9 days. After 7 days of treatment, treated groups were exposed by hepatotoxic dose of paracetamol (2000 mg/kg BW). The SGPT and SGOT activity of all groups was measured by enzimatic assay. The result can be concluded that Syzygium campanulatum extract was found to be active as hepatoprotective agent with 210 mg/kg BW dosage (SGPT 21.76 ± 3.98 U/L and SGOT 7.32±6.74U/L) as eff ective as with the curcuma tablets (SGPT 23.91 ± 4.41 U/L and SGOT 14.12±5.37 U/L) and the hepatoprotective activity of Syzygium campanulatum extract at a dosage 420 mg/kg BW better than curcuma tablets (SGPT 12.43 ± 6.51 U/L and SGOT 6.64 ± 5.88 U/L). While the hepatoprotective activity of Syzygium aromaticum extracts eff ective as with curcuma tablets at all dosage variation.